PEMENUHAN HAK KORBAN PELANGGARAN GENOSIDA DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 26 TAHUN 2000 TENTANG PENGADILAN HAK ASASI MANUSIA - Muhammad Zulfikar Andhikarani (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTHuman rights violations Genocide is an extraodinary crime that resulted in the loss of material and immaterial victims. Victims who have suffered  Genocide often do not get the protection and fulfillment of the rights held in accordance with the provisions of applicable law. Based of the results of this writing, it can be known that the victims of human rights vioations Genocide according to the provisions of legislation appicable have the right to get protection, compensation, restution, and rehabilition. Efforts should be made to address contained in the fulfillment of the rights of victims is by absorbing covenants International human rights into national law, make repairs regulations regarding the rights of victims, increased support for the house of representatives, the manufacturing bill handling of cases of human rights violatons Genocide and icreasing the presindent’s role in the formation of the court human rights Ad Hoc.Keyword : Rights, Victims, Human Rights Genocide.